Dynamic co-integration between foreign workers and unemployment in Malaysia - Mohd Shahidan, Shaari; Abdul Rahim, Ridzuan; Faiz, Masnan; Nur Salimah, Alias (Inderscience Enterprises Ltd., 2024)
This study attempts to investigate the effect of foreign workers on unemployment in Malaysia. Data ranging from 1982 to 2018 were analysed by using the ARDL approach. The results show that a higher number of foreign workers does not have any impact on unemployment in the short run and long run in Malaysia. Therefore, an increase in the number of foreign workers into Malaysia does not affect the native labour force. This is because some critical sectors, such as construction, need foreign workers to ensure that the activities of the sectors are not affected due to the shortage of labour. Native workers do not favour jobs in the sectors owing to low payment. The Ganger causality results, on the other hand, show that migration can influence unemployment in the country. Therefore, these findings can shed light on the issue for policymakers to formulate the right policies.